Variable speed control of a permanent magnet synchronous motor drive without mechanical sensors - Guo, Xiuli. (2010)
Permanent Magnet Synchronous motors (PMSMs) have been used in a wide range of applications due to their high torque to inertia ratio, higher power density and efficiency. To drive the motor, the instantaneous rotor position is needed to perform electronic commutation. This is normally achieved by using position encoder or resolver mounted onto the motor shaft. Due to the disadvantages and limitations of the mechanical position sensors, there has been an increasing interest in developing techniques for eliminating the position sensors to improve reliability and to reduce the cost of the drive system.